The Analysis of Components on Monolingual Spanish Learner’s Dictionaries for Foreign Students - Jittho, Arthit (Pattimura Excellence Journal of Language and Culture, 2022)
Dictionaries have been considered as one of major tools for foreign language learning. So, this study aimed to analyze the main elements of monolingual Spanish learner’s dictionaries for foreign students. The study used the comparative study approach to examine components of each dictionary in making the acquaintance of their key components used in three Spanish studied dictionaries, namely, 1.) Diccionario para la Enseñanza de la Lengua Española (DIPELE), 2.) Diccionario Salamanca de la Lengua Española (DSLE), 3.) Diccionario Español para Extranjeros (DEESM). The analysis was applied to the search mode, the selection of corpus, provided grammatical notes and other useful features in the three dictionaries. The results revealed that all of the analyzed dictionaries possess some key features in common designed to enhance language learning and some of them provided some helpful language advice